TRANSFORMASI MINAT BELAJAR MURID KELAS IV SD MELALUI IMPLEMENTASI APLIKASI FUN LEARNING GAME - Prista Olga Virmawan; Wiryanto; Julianto (JS (JURNAL SEKOLAH), 2026)
Abstract: This article aims to describe the transformation of learning interest among fourth-grade elementary school students through the implementation of the Fun Learning Game application as a game-based learning medium. The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group type, involving an experimental class and a control class. Data on learning interest were collected using a Likert scale questionnaire and analyzed using inferential statistics. The results of the study showed a significant increase in learning interest among students in the experimental class, especially in terms of active involvement, interest in the media, and intrinsic motivation. These findings confirm that Fun Learning Game is an effective and relevant innovative medium for IPAS learning in elementary schools. Keyword: Learning Interest, Fun Learning Game, Game-Based Learning, IPAS, Elementary School   Abstrak: Artikel ini bertujuan mendeskripsikan transformasi minat belajar murid kelas IV SD melalui implementasi aplikasi Fun Learning Game sebagai media pembelajaran berbasis game-based learning. Penelitian menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen tipe non-equivalent control group design yang melibatkan kelas eksperimen dan kelas kontrol. Data minat belajar dikumpulkan melalui angket skala Likert dan dianalisis menggunakan statistik inferensial. Hasil penelitian menunjukkan peningkatan minat belajar yang signifikan pada murid kelas eksperimen, terutama pada aspek keterlibatan aktif, ketertarikan terhadap media, dan motivasi intrinsik. Temuan ini menegaskan bahwa Fun Learning Game merupakan media inovatif yang efektif dan relevan untuk pembelajaran IPAS di Sekolah Dasar. Kata Kunci: Minat Belajar, Fun Learning Game, Game-Based Learning, IPAS, Sekolah Dasar